THE IMPACT OF CLIENT COMPANY SIZE, TIME BUDGET PRESSURE AND AUDITOR FREE ON AUDIT QUALITY IN PHARMACEUTICAL SUB-SECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE (IDX) PERIOD 2017-2021 - Wibowo, Yudi (Journal of Accounting, Entrepreneurship and Financial Technology (JAEF), 2023)
This study aims to determine the effect of the variables Client Company Size, Time Budget Pressure and Auditor Fee on Audit Quality. The information utilized in this examination was procured from the Consolidated and Yearly Fiscal Summaries accessible on the Indonesia Stock Exchange (IDX) site. The technique of investigation executed is logistic regression analysis, tested jointly with the overall model fit test which has a significant effect on audit quality. The results of this study indicate that of the three independent variables analyzed, The quality of audit is considerably impacted by the pressure of time and budget, as well as the fee charged by the auditor. However, the magnitude of the client company does not seem to significantly affect the audit quality. The Nagelkerke R Square value indicates that 91.2% of the dependent variable's variability can be explained by the independent variables, whereas the remaining 8.8% is attributed to other variables beyond the research model.